Description of Asiothrixus gen. nov. (Hemiptera: Aleyrodidae) and two new species with diagnoses and a puparial key to species - Dubey, Anil Kumar; Ko, Chiun-Cheng; Martin, Jon H. (Zootaxa, 2010)
A new Asian genus is diagnosed, Asiothrixus, with Aleurothrixus antidesmae Takahashi as type species, together with Asiothrixus smilaceti (Takahashi) comb. nov., Asiothrixus silvestris (Corbett) comb. nov., Asiothrixus specialis sp. nov. and Asiothrixus unicus sp. nov. Lectotypes are designated for both A. antidesmae and A. smilaceti. Characteristics of the new genus are discussed, and puparial diagnoses and illustrations for the species provided, together with a puparial key to species.